Targeting epidermal growth factor receptor: An important strategy in oncology - MAHESH G. KHARATMOL; DEEPALI M. JAGDALE (International Journal of Pharma and Bio Sciences, 2017)
Epidermal growth factor receptor (EGFR) is a transmembrane receptor tyrosine kinase included in the Human Epidermal Receptor (HER) family plays an essential role in signal transduction pathways that regulate differentiation and cell division which causes normal organ development by mediating morphogenesis and differentiation through effects on apoptosis, cell proliferation, differentiation, invasion, and angiogenesis. The role of EGFR is to help maintain mucosal integrity, aid in mucosal repair in the gut, and maintain the protective barrier of the skin. Unlike normal cells that have tight regulatory mechanisms controlling EGFR pathways, tumor cells often have dysregulated EGFR signaling, allowing them to proliferate under adverse conditions, invade surrounding tissues, and increase angiogenesis. Epidermal growth factor can be found in saliva, macrophages, urine, plasma and milk. EGFR inhibitors are used to treat pancreatic cancer, non-small-cell lung cancer, colon cancer, breast cancer and some other cancers which show epidermal growth factor receptor up-regulation. Various heterocyclic scaffolds which have been reported as EGFR inhibitors in literature are pyrazoline, isoquinoline, quinoxalline, pyrimidine, indole and purine derivarives. Considering the importance of EGFR in targeted anticancer treatment, in the present article we are emphasizing on various targeted therapies, role of EGFR in cell growth, mechanism of action of EGFR inhibitors, structural requirements, resistance of the EGFR inhibitors based upon the literature survey.